COVID-19 and human rights: a new inseparable relationship - Maltez Alberto Mabuie (International Journal of Communication and Society, 2021)
The COVID-19 pandemic is arguably the most severe pandemic of the last century and has completely transformed how people go about their lives. With a high infection rate and no known cure yet, different countries have had to adopt extraordinary measures to curtail the spread of the virus. In particular, multiple countries have imposed lockdowns. The lockdowns have inadvertently interfered with human rights previously enjoyed by people, such as freedom of movement and the right to food, water and sanitation.We conducted an exploratory, non-systemic review of peer-reviewed journal articles, published between 2015 and 2020. The explored databases included: Ebscohost, Google Scholar, Wiley, JAMA, Elsevier, Oxford, CDC and Medline/PubMed.Our review of the literature highlighted the importance of states adopting a human-rights-centric approach in their responses to the Covid-19 pandemic. Three main thematic dimensions of various nations’ responses to the Covid-19 were constructed to represent this review. The three are human rights, gender inequality and social stigma.Some of the reactions to the Covid-19 pandemic have brought about the infringement of human rights. While some of the measures are justified, there is a need to ensure that human rights are protected to prevent states of the world abusing executive orders and emergency powers. This need set aside, crises, such as the COVID-19 pandemic, usually affect men and women differently. Such crises may even exacerbate the existing gender inequalities in society. Therefore, this calls for governments to devise measures to protect vulnerable populations such as women and children during the pandemic.